2003
DOI: 10.1002/jcc.10344
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical PM5 molecular orbital study on chlorophylls and bacteriochlorophylls: Comparison of semiempirical, ab initio, and density functional results

Abstract: The semiempirical PM5 method has been used to calculate fully optimized structures of magnesium-bacteriochlorin, magnesium-chlorin, magnesium-porphin, mesochlorophyll a, chlorophylls a, b, c(1), c(2), c(3), and d, and bacteriochlorophylls a, b, c, d, e, f, g, and h with all homologous structures. Hartree-Fock/6-31G* ab initio and density functional B3LYP/6-31G* methods were used to optimize structures of methyl chlorophyllide a, chlorophyll c(1), and methyl bacteriochlorophyllides a and c for comparison. Spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 62 publications
(110 reference statements)
8
80
0
Order By: Relevance
“…Compared to the former, the latter method overestimates by a factor of 2-3 both the excitation energies and the broadening of the energy spectrum. Just like in several previous studies, 19,20,45,46 we have found that the ZINDO/S method repeatedly yields results in good agreement with existing experimental data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to the former, the latter method overestimates by a factor of 2-3 both the excitation energies and the broadening of the energy spectrum. Just like in several previous studies, 19,20,45,46 we have found that the ZINDO/S method repeatedly yields results in good agreement with existing experimental data.…”
Section: Discussionsupporting
confidence: 90%
“…43,44 Because it is much faster and more accurate than most of the computationally affordable ab initio QC methods ͓e.g., the Hartree-Fock ͑HF͒ CIS method with the minimal STO-3G * basis set͔, ZINDO/S CIS has been extensively used in the literature to compute low lying optically allowed excited states of pigment molecules. 19,20,45,46 In cases like ours, where thousands of QC calculations are required, the proper balancing between speed and accuracy is absolutely essential. To further increase the computational speed, the active orbital space for the CIS calculations was restricted to the ten highest occupied molecular orbitals ͑HOMOs͒ and the ten lowest unoccupied molecular orbitals ͑LUMOs͒.…”
Section: B Quantum Chemistry Calculationsmentioning
confidence: 99%
“…57 In general, exceptionally good performance of the PM5//ZINDO/S scheme (i.e., PM5 geometry optimization followed by a ZINDO/S single-point energy calculation) is found for the Mg complexes of unsubstituted porphyrin, chlorin and bacteriochlorin as well as Chls and BChls. 56 The PM5 optimized structures of unligated and 6-coordinate complexes predicts a planar porphyrin with the Mg in the 4N-plane, whilst 5-coordinate species show a substantial out-of-plane displacement of the Mg atom, in line with both B3LYP and HF/6-31g*. Additionally, all methods correctly predict that the Mg-N bond(s) to the reduced rings are longer than those from non-reduced rings.…”
Section: Methodsmentioning
confidence: 60%
“…Partial atomic charges were also found to be consistent amongst the semiempirical, HF and DFT methods. 56 Overall, the best transition energies were obtained using the B3LYP/6-31g*//ZINDO/S scheme. However, PM5//ZINDO/S was also considered to perform well and was recommended for use in large calculations where the more accurate and expensive B3LYP/6-31g* optimizations are impractical.…”
Section: Methodsmentioning
confidence: 99%
“…For Chl and BChl a and c it was shown that the HF method results in larger bond-length alternation than DFT/B3LYP. The maximal difference in CÀC bond length within the porphyrin ring lies between 0.011 for Chl c 1 and 0.044 for BChl c. [92] These structures lead to higher excitation energies than those optimized with DFT. [92] Another striking optimization effect was found for the native Chl pigments.…”
Section: Optimization Of Input Structuresmentioning
confidence: 97%